Effects of Zr4+ Doping on the Electrochemical Characteristics of Li2FeP2O7/C in Lithium Ion Batteries. Issue 13 (1st January 2017) - Ryu, Da-Jeong; Lee, Seong-Hun; Ryu, Kwang-Sun
Abstract : Using splash combustion synthesis, Zr 4+ -doped Li2 Fe1-x Zrx/2 P2 O7 /C (x = 0, 0.01, 0.02, 0.03, and 0.04) composites were successfully synthesized in order to increase the redox voltage and c-rate performance. X-ray diffraction (XRD) patterns indicated that the successfully obtained Li2 Fe1-x Zrx/2 P2 O7 /C had a monoclinic structure. The results indicated that the zirconium atoms within the Zr 4+ -doped system do not change the lattice structure of Li2 FeP2 O7, but do enlarge the lattice volume. During the de-intercalation and intercalation of lithium ions, the doped zirconium atoms protect the Li2 FeP2 O7 structure from spontaneous structural rearrangement, which can lower the reaction potential. Among the various samples, Li2 Fe0.97 Zr0.015 P2 O7 /C exhibited excellent rate and cycling performance. We investigated the electrochemical performance and lithium ionic diffusion coefficient by using three electrochemical perturbation methods: cyclic voltammetry (CV), galvanostatic intermittent titration technique (GITT), and potentiostatic intermittent titration technique (PITT). Li2 Fe0.97 Zr0.015 P2 O7 /C exhibited relatively good electrochemical performance in comparison with Li2 FeP2 O7 /C. We further investigated the lithium ion diffusion behavior by using CV, GITT, and PITT. Li2 Fe0.97 Zr0.015 P2 O7 /C demonstrated more rapid ionic diffusion than Li2 FeP2 O7 /C did due to its higher diffusion coefficient value. Therefore, these ionic kinetic studies were helpful to understand the enhanced electrochemical performance.